Feed Solution Characterization - Nidal Hilal (Membrane Characterization, 2017)
Membrane processes are advanced filtration processes that utilize the separation properties of finely porous polymeric or inorganic films. Membrane separations are used in a wide range of industrial processes to separate biological macromolecules, colloids, ions, solvents, and gases. To design, develop, and model membrane processes, knowledge of the physical properties of the solution to be separated is paramount. These properties influence the choice of membrane and process conditions for optimal use. For liquid-based membrane separations the important properties are particle size, surface charge (or zeta potential), and solution viscosity. In this chapter methods for characterizing solution properties will be discussed.